Sericea Lespedeza Control Strategies Differ in Their Impacts on Overall Range Health and Native Plant Species Composition - G. A. Gatson; W. H. Fick; W. W. Hsu; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective of this study was to evaluate the effects of sericea lespedeza (Lespedeza cuneata) control strategies of late summer prescribed burning and fall herbicide application on soil cover, native plant populations, and biological diversity. Study Description:We established 16 individual units within an 80-acre native tallgrass pasture. Each unit was assigned to 1 of 4 treatments: control, spray only, burn only, or burn-plus-spray. Burn only and burn-plus-spray units were burned in early September. Spray only and burn-plus-spray units were sprayed with metsulfuron methyl (Escort XP, DuPont, Wilmington, DE) in late September. The change in soil cover and plant community composition from prior to treatment application to 1 year after treatment was measured. The Bottom Line:The benefits of curbing a major invasion of sericea lespedeza may make burn-plus-spray a desirable short-term strategy in some instances, but widespread or extended use of the practice should be applied with caution.
Keywords: prescribed burning; sericea lespedeza; tallgrass prairie